2019
DOI: 10.1007/s10237-019-01266-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm to predict bone changes in the mouse tibia properties under physiological conditions

Abstract: Understanding how bone adapts to mechanical stimuli is fundamental for optimising treatments against musculoskeletal diseases in preclinical studies, but the contribution of physiological loading to bone adaptation in mouse tibia has not been quantified so far. In this study, a novel mechanistic model to predict bone adaptation based on physiological loading was developed and its outputs were compared with longitudinal scans of the mouse tibia. Bone remodelling was driven by the mechanical stimuli estimated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 38 publications
5
35
0
Order By: Relevance
“…Nevertheless, excellent correlation was found between the structural properties predicted with hexahedral or tetrahedral models, highlighting that the geometry was consistently modelled with the two mesh types. However, such differences in local strains may affect the prediction of bone remodelling based on local mechanoregulation (Cheong et al 2020a , b ) and should be considered when designing multi-scale computational models. The material properties assignment mainly affected the correlation between experimental and predicted structural properties, as models with the same material properties resulted in similar slopes of the regression lines (Table 3 , Supplementary material 5).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, excellent correlation was found between the structural properties predicted with hexahedral or tetrahedral models, highlighting that the geometry was consistently modelled with the two mesh types. However, such differences in local strains may affect the prediction of bone remodelling based on local mechanoregulation (Cheong et al 2020a , b ) and should be considered when designing multi-scale computational models. The material properties assignment mainly affected the correlation between experimental and predicted structural properties, as models with the same material properties resulted in similar slopes of the regression lines (Table 3 , Supplementary material 5).…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be due to the asymmetry in bone remodeling activities as observed with in vivo microCT imaging of the mouse tibia (Roberts et al, 2019). However, it needs to be further explored if this difference can be associated with the loading condition due to the effect of the curvature of the bone, as under physiological compressive loads a peak of compressive strains is located on the medial surface of the tibia below the tibio-fibular junction (Oliviero et al, 2018;Cheong et al, 2020). Nevertheless, this difference was not observed in Balb/C mice, which have a similar geometry of the mouse tibia but lower curvature.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, simulating the distribution of strain energy density (SED)—defined as the increase in energy associated with the tissue deformation per unit volume (i.e., a measure of direct cell strain) —within the caudal vertebrae revealed that bone formation was more likely to occur at sites of high SED, whereas bone resorption was more likely to occur at sites of low SED ( Schulte et al, 2013 ; Lambers et al, 2015 ). While SED is widely used as a mathematical term to describe the mechanical signal influencing bone (re)modeling ( Huiskes et al, 2000 ; Schulte et al, 2013 ; Birkhold et al, 2017 ; Cheong et al, 2020 ), other mechanical signals, such as interstitial fluid flow through the lacuna-canalicular network (LCN), are also known to play a major role in determining the local mechanical environment surrounding osteocytes, the main mechanosensors in bone ( Fritton and Weinbaum, 2008 ; Weinbaum et al, 2011 ; Klein-Nulend et al, 2013 ). In this respect, it has been suggested that measures of fluid flow, such as the gradient in SED, would allow improved predictions of adaptive bone (re)modeling events ( Webster et al, 2015 ; Tiwari et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%